The effectiveness of arbuscular mycorrhizal fungi inoculation on growth performance of cocoa (Theobroma cacao L) seedlings / Siti Noor Baiezura Othman - Othman, Siti Noor Baiezura (Faculty of Plantation and Agrotechnology, 2015)
A polybag experiment was conducted under rain shelter to evaluate the growth performance of Theobroma cacao seedlings with inoculation of arbuscular mycorrhizal fungi and to identify the different level of arbuscular mycorrhizal fungi in the growth performance of cocoa seedling. Cocoa seedling of hybrid VI T1 x Na32 was used and was inoculated with different rate of mycorrhiza which is 15g, 30g, 45g, 60g, 75g, and 90g and uninoculated as a negative control and 5g of CIRP as a positive control. The experiment was a single factor experiment arranged in a completely randomized design with four replications. Of the eight treatment used, plants inoculated with 90g of mycorrhiza gave more pronounced and significant vegetative growth Maximum plant height no of leaves stem diameter, fresh root and dry root weight of 51.8cm, 46.8, 13.3mm, 123.6g, and 50.lg respectively were obtain from seedling inoculated with 90g of arbuscular mycorrhiza.